Annealing effect on temperature stability and mechanical stress at the “CdxPb1−xS film – substrate” interface - L. N. Maskaeva (Uralʹskij federalʹnyj universitet imeni pervogo Prezidenta Rossii B.N. Elʹcina, 2020)
The article establishes the upper temperature steadiness limit of СdxPb1-xS supersaturated solid solutions obtained by chemical bath deposition. СdxPb1-xS (x = 0.06; 0.122; 0.176) and (x = 0.02–0.05) films remained stable under the heating up to 405–410 and 450 K, respectively. SEM studies have shown that heating of СdxPb1-xS films (x = 0.02–0.05) to 620 K leads to the structure destruction. Internal mechanical compressive stresses at the "СdxPb1-xS film-substrate" interface was calculated in the range of 300–900 K for the first time ever, the highest values reached 2000–2750 kN/m2 for a number of the films compositions. In contrast to solid solutions, the expansion stresses up to 100 kN/m2 were derived for the CdS layer at 900 K. The obtained temperature steadiness boundaries and the mechanical stresses of СdxPb1-xS films must be taken into account in the development of photonic devices based on such materials.